2018
DOI: 10.15561/20755279.2018.0407
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of repeated static apnea on aerobic power

Abstract: Purpose: Apnea exercises cause a rise in hematocrit, erythropoietin, hemoglobin concentration, lung volume and oxygen store in muscle and blood, and a decrease in blood acidosis and oxidative stress. These types of physiological changes that occur in the body result in developments in both time to exhaustion and V02max. The purpose of the current study was to investigate the acute effect of repeated static apneas on aerobic power. Material: Twenty physically active male university students (age:22.80±3.84 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
2
3
0
1
Order By: Relevance
“…However, the increased blood pressure and peripheral vasoconstriction might impair performance. Studies evaluating the effect of apneas on performance found no improvement (Du Bois et al, 2014;Sperlich et al, 2015;Yildiz, 2018). In consistence with these studies, the WHBM did not enhance performance in this investigation.…”
Section: Diving Responsesupporting
confidence: 65%
See 1 more Smart Citation
“…However, the increased blood pressure and peripheral vasoconstriction might impair performance. Studies evaluating the effect of apneas on performance found no improvement (Du Bois et al, 2014;Sperlich et al, 2015;Yildiz, 2018). In consistence with these studies, the WHBM did not enhance performance in this investigation.…”
Section: Diving Responsesupporting
confidence: 65%
“…BH also triggers the so-called "diving response" (Foster and Sheel, 2005), which includes bradycardia, peripherical vasoconstriction, increased blood pressure, and contraction of the spleen (Dujic et al, 2011). The latter releases ∼100 ml of concentrated red cells into the circulation, which may influence performance, even though most investigations did not find improvement in performance following apneas (Du Bois et al, 2014;Sperlich et al, 2015;Yildiz, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted over the past 3 years, it was noted that an athlete's body type also affects their athletic achievements (Kutseryb et al, 2019; Rybakova et al, 2020). However, based on the analysis of reports on the health status of adolescents and students, considering their constitutional characteristics, a conclusion was made about one of the problems of modern youth (Yıldız, 2018). Namely, their lifestyle often leads to hypodynamia—a violation of body functions conditioned by limited physical activity (Zurita‐Ortega et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…BH also triggers the so-called "diving response" (Foster and Sheel, 2005), which includes bradycardia, peripherical vasoconstriction, increased blood pressure, and contraction of the spleen (Dujic et al, 2011). The latter releases ∼100 ml of concentrated red cells into the circulation, which may influence performance, even though most investigations did not find improvement in performance following apneas (Du Bois et al, 2014;Sperlich et al, 2015;Yildiz, 2018).…”
Section: Introductionmentioning
confidence: 99%